The development of abortion in China : a social legal study - Wang , Xiaoxin (Fakulti Undang - Undang, 2007)

(untitled)
Since 1989, western countries and human rights organizations have been criticizing the situation of China’s human rights by coercive abortion and later termed abortion. Most of these criticisms are unreasonable accusations and have their own political agenda. The purpose of this article is to illuminate the essentials of the policies of abortion, and to predict the future of these policies, in order for people from other jurisdictions to understand such policies correctly and objectively. In this article, China’s history of abortion and the development of abortion will be highlighted, and China’s laws and regulations will be analysed. Based on these development and analysis, readers can understand why china allows women to perform induced abortion, the propose and background of legislation regarding abortion, the shortcoming of the policy and how to improve it, Furthermore, this article will also propose some suggestions to improve current policy, and reveal the future of China’s abortion. Finally, the whole article will emphasis particularly on the issue of population, because the population is the primary factor for the policy of abortion in China